Between theory and practice: social workers' views: https://doi.org/10.53809/2021-01-TS-n.1-89-103 ("Temas Sociais" Journal, 2021)
Today, we live in a phase of scientific development of social work, and it is crucial to discuss the importance of a practice that works in harmony with theory. In this sense, this study aims to understand the different theoretical perspectives that frame the professional practice of a sample of Portuguese Social Workers based on Malcolm Payne's tripartite perspective. An online questionnaire was applied to a sample of 54 Social Workers, in the year of 2018. The results show that the majority of Social Workers position themselves in an Individualist-reformist and Therapeutic-reflexive vision and only a minority in the Socialist-collectivist or mixed vision.
Keywords: social work; theoretical models of social work; professional identity